Rancang Bangun Sistem Informasi Persediaan Barang Pada Pt. Bumi Permata Medika - Mahmud Safudin; Andrian Eko Widodo; Eko Yulianto; Supriatiningsih Supriatiningsih (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - In running a medical equipment Inventory report PT. Bumi Permata Medika can still work conventionally, there are have problems in making reports. The number of stocks, the name of the item that must be recorded, causes data to be mixed and the need for a relatively longer time to do it, it must be done carefully. Lack of accurate information causes companies not to know the minimum storage limits and stages of medical equipment inventory for the next period. To overcome the problem at PT. Bumi Permata Medika in the supply of medical devices, the author makes information system inventory of medical devices using the program. To simplify the work in processing data on medical supplies that are useful. The system development method used in designing this information system is the system development life cycle (SDLC) method. Keywords: information System, inventory, SDLC